2016
DOI: 10.1007/978-3-319-47874-6_20
|View full text |Cite
|
Sign up to set email alerts
|

What am I not Seeing? An Interactive Approach to Social Content Discovery in Microblogs

Abstract: Abstract. In this paper, we focus on the informational and user experience benefits of user-driven topic exploration in microblog communities, such as Twitter, in an inspectable, controllable and personalized manner. To this end, we introduce "HopTopics" -a novel interactive tool for exploring content that is popular just beyond a user's typical information horizon in a microblog, as defined by the network of individuals that they are connected to. We present results of a user study (N=122) to evaluate HopTopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this regard, the work of [9] is pertinent, showing how visualisation could increase user awareness of the filter bubble, understandability of the filtering mechanism, and a user's sense of control over their data stream. In another study users were able to control which people in their immediate and extended network contributed to their information feed on Twitter, and the findings suggest that the interface increased users' sense of transparency and control [8].…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…In this regard, the work of [9] is pertinent, showing how visualisation could increase user awareness of the filter bubble, understandability of the filtering mechanism, and a user's sense of control over their data stream. In another study users were able to control which people in their immediate and extended network contributed to their information feed on Twitter, and the findings suggest that the interface increased users' sense of transparency and control [8].…”
Section: Related Workmentioning
confidence: 98%
“…This work addresses the issue of filter bubbles by helping users understand not only why a recommendation was made, but also convey the limits of this recommendation. Previous work on answering the why question has led to considerable recent research on explaining recommendations (e.g., [3,8,11]), but the issue of framing the limits of a recommendation is relatively under-examined.…”
Section: Related Workmentioning
confidence: 99%
“…Webster and Vassileva (2007) propose a news recommender system with a twist: it is accompanied by a visual map of yourself in relation to other users in your social network, whom you can place closer or farther away from yourself to change their own influence on what you see, as well as take a glimpse into the kinds of recommendations they will be getting. Kang et al (2016) propose a similar system for Twitter users to explore content 'popular just beyond a user's typical information horizon' . Here, the focus is less on 'why did I get this recommendation?'…”
Section: Passive Interventions: Profiles In Perspectivementioning
confidence: 99%
“…We will also continue to build on our previous work on explanation interfaces that used weak ties to support content discovery [14,23], to study the role of item positions in relation to perceptions of diversity. By defining diversity in a way that is understandable and acceptable to users, it becomes possible to move research on explanation-aware recommendation to the next level: how we present diverse items in recommender systems can help users not only to understand the recommendations, but also themselves and their own biases.…”
Section: Discussionmentioning
confidence: 99%
“…The first approach is to help users to better understand the recommended items relative to a wider set of candidate items. Taking this approach, we have found that helping users control which people contributed to their information feed on Twitter increased their sense of transparency and control [14,23]. However, we also found that users had a poor mental model for the degree of novel content discovered when presented with non-personalized tweets, and thus potentially more challenging, information.…”
Section: Related Workmentioning
confidence: 99%